2008
DOI: 10.1038/jp.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Severe retinopathy of prematurity and visual outcomes in British Columbia: a 10-year analysis

Abstract: Objective: To describe the incidence trend and long-term visual outcomes of infants diagnosed with stages 3 to 4 retinopathy of prematurity (ROP) or laser-treated ROP born in British Columbia (Canada).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…A study by Schiariti et al 1 demonstrated an increase in ROP as well as severe ROP without changes in the incidence of VI when comparing neonates born in 1992–1996 and 1997–2001. Slidsborg et al 5 found a more than twofold increase in the incidence of treated ROP cases born in Denmark from 2001 to 2005 compared with 1996–2000.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Schiariti et al 1 demonstrated an increase in ROP as well as severe ROP without changes in the incidence of VI when comparing neonates born in 1992–1996 and 1997–2001. Slidsborg et al 5 found a more than twofold increase in the incidence of treated ROP cases born in Denmark from 2001 to 2005 compared with 1996–2000.…”
Section: Discussionmentioning
confidence: 97%
“…1,000 g admitted in the Stockholm area of Sweden in the period 1998-2000, compared to 1988-1990. Hameed et al [14] and Schiariti et al [16] reported an increase in the incidence of severe ROP in infants with a birth weight ! 1,250 g in the county of Leicestershire, United Kingdom and British Columbia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several mainly population-based studies on the incidence of ROP have been performed, both retrospective and prospective [4][5][6][14][15][16] . Comparison of these studies with each other as well as with our study is difficult because entry criteria vary, as well as methods, survival rate and population demographics.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the examinations are performed by experienced ophthalmologists, they often are stressful for the infants. [11][12][13] Moreover, ϳ90% to ϳ95% of those examined never need any treatment, 10,14 according to current recommendations, and thus do not benefit from screening except for learning that they do not have disease and do not need treatment. More cost-effective programs are needed to identify, before the development of ROP, infants at high and low risk for disease.…”
mentioning
confidence: 94%